Analysis of Collision Hazard Prevention With Operating Radar NICD – 453 Type On MV Amrta Jaya 1 - Slamet Prasetyo Sutrisno; Siti Nurlaili Triwahyuni; David Ardiansyah (IWTJ : International Water Transport Journal, 2022)
The navigation system is the key to the safety of the ship in carrying out the voyage. RADAR will be very useful during bad weather, foggy conditions and sailing at night, especially when navigational instructions such as beacons, buoys, hills or buildings cannot be visually observed. So prospective ship officers must understand and understand to use RADAR navigation tools. To find out the target position and reduce the accident rate in the shipping lane, the role of RADAR in supporting shipping safety is needed. This study aims to analyze the prevention of collision hazards by using the Maneuvering Board in the operation of the Binocular RADAR at MV AMRTA JAYA 1. The type of research used in this study is quantitative research. In this case the data collection techniques used are documentation and observation. Documentation is in the form of searching for information in the form of books and documents, while observation is in the form of an approach to the object of research. From the results of research conducted, it can be seen that the method used to calculate the RADAR Plotting Sheet can be done by theoretical methods with formulas and scale methods with mathematical logic. The two methods can be used with the same results but with different time efficiency. The use of muvering boards and RADAR Plotting Sheet calculations can help identify the presence or absence of a collision hazard, and help estimate the closest distance, time taken, course and speed of the target ship.